PENGARUH PENGGUNAAN MEDIA VIDEO DONGENG TERHADAP KEMAMPUAN KOMUNIKASI SISWA KELAS III SD INPRES HOMBES ARMED KABUPATEN GOWA - Sartika Syam; Satriawati; Bellona Mardhatillah Sabillah; Waddi Fatimah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to determine the effect of using fairy tale video media on the communication skills of Class III students at SD Inpres Hombes Armed. This research uses a quantitative approach and a nonequivalent control group design experimental research type. The sample for class III A consists of 36 students and III B consists of 36 students. The research instruments used were questionnaire observation sheets and learning outcomes tests. Analysis of descriptive data, researchers found that the communication skills of fairy tale video media and fairy tale text through three indicators of effective learning, namely for student activity in the experimental class 4.2 (very good) while for the Control class 3.85 (good), student responses for the experimental class 4.6 (Very good) while for the Control class 3.5 (good) and learning outcomes for the experimental class 4.2 (very good) while for the Control class 3.5 (good). Analysis of inferential statistical data for the experimental class, the significant value of the fairy tale video pre test (0.020), fairy tale video post test (0.003), and fairy tale text pre test (0.009) was below 0.05 so it could be concluded that it did not meet the assumption of normality. Because not all variables meet the normality assumption, the homogeneity value is 0.082, the hypothesis test used is the Wilcoxon and Mann Whitney test, with a significant value of 0.007, which has a value smaller than the 0.05 significance level, meaning there are differences in students' communication abilities.